Uplifting the well-being of teacher candidates through virtual exchange during COVID-19 - Shannon Hilliker; Barbara Loranc; Devindi Samarakkody (University of Groningen Press, 2022)
COVID-19 is a time of adversity for college students. Different universities have taken different measures to uplift student well-being. Virtual exchange was a tool that improved student well-being, relieved distress, and helped students focus on their studies. This virtual exchange that partnered teacher candidates outlines how effective this measure was for the participants during COVID-19. This study explores how virtual exchange impacted the well-being of teacher candidates when their university classes were moved online. The data for this research were obtained from a questionnaire, with qualitative and quantitative components, given to the teacher candidates of two universities at the end of the semester regarding their experience interacting virtually throughout the semester. Interacting with a virtual partner when all the classes moved online when less in-person interaction was available benefited students in uplifting wellbeing in terms of Positive emotions, Engagement, Relationships, Meaning and Purpose, and Accomplishment (PERMA).